An Interdisciplinary Approach to 'Newness' in Historical Populations. - Acres, William (International Journal of the Humanities, 2005)
In the creation of application for computing, and interdisciplinary team of scholars has grappled with a threefold series of questions. First, the method of creating a data analysis of points of contact (to use Geoffrey Elton's phrase) which existed historically, and which exists in present and future tenses. The graphing of tabular information of individuals (military cohorts from the late-Sixteenth Century) presents a different approach to the historiographic problem of the ‘Military Revolution’ — a congeries of new knowledge and knowledge communities linked by publication, personal and family ties, the Court, the county, the Universities, and by reading, copia, and other personal and corporate identities. Second, the method of tabulating these lives as institutional entities drawn from manuscript and printed sources will be analyzed as a dynamic construct of the individual ontologies of the military group, even as a larger sense of change can be detected in the transmission of cultural knowledge. In conclusion, the nature of the transmission of knowledge and culture will be summarized with respect to the data and the introduction of an application for computing.